A furious sky : the five-hundred-year history of America's hurricanes - Dolin, Eric Jay (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2020)
"The best-selling author of Leviathan returns with the first major historical account of America's hurricanes, and reveals how they've shaped our nation. From the moment European colonists laid violent claim to this land, hurricanes have had a profound and visceral impact on American history-yet, no one has attempted to write the definitive account of America's entanglement with these meteorological behemoths. Now, best-selling historian Eric Jay Dolin presents the five-hundred-year story of American hurricanes, from the nameless storms that threatened Columbus' New World voyages, to the devastation wrought by Hurricane Maria in Puerto Rico and the escalation of hurricane season as a result of global warming. Populating his narrative with unlikely heroes such as Benito Vines, the nineteenth-century Jesuit priest whose revelatory methods for predicting hurricanes saved countless lives, and journalist Dan Rather, whose coverage of a 1961 hurricane would change broadcasting history, Dolin uncovers the often surprising ways we respond to natural crises. A necessary work of environmental and cultural history, A Furious Sky will change the way we understand the storms on the horizon of America's future"--